The Role of Kaloka Art Studio in Traditioning Slendang Pemalang Dance as The Region Identity in Pemalang District - Wahyuni, Eko; Hartono, Hartono (Universitas Negeri Semarang, 2018)
Kaloka Art Studio is a place to learn art, especially dance. Kaloka Art Studio is a studio that traditioning Slendang Pemalang Dance which become the pride of Pemalang Regency society. The problem in this study are (1) how is the embodiment of Slendang Dance is a depiction of regional identity and (2) how is the role of Kaloka Art Studio in traditioning Slendang Dance as the regional identity. The objective of this study is to asses the embodiment of Slendang dance and analyze the role of Kaloka Art Studio in traditioning the Slendang Pemalang Dance. This study uses qualitative approachment. The data collection techniques including observation, interview and documentation. Data analysis are using data reduction, data serving and conclusion. The result of this research is the manifestation of Slendang Pemalang Dance as regional identity. The role of Kaloka Art Studio in traditioning Slendang dance has been done through training and dance performances. Training Studio as a model of non-formal learning. The conclusion of this research are (1)the embodiment of Slendang Pemalang Dance according tonthe dance element which is wiraga, wirama , wirasa and costume according to the characteristic of the Pemalang society; (2) the role of Kaloka Art Studio in traditioning the dance through socialization, training and performance of the dance.